The tongue microbiome in healthy subjects and patients with oral diseases: The first study in Algeria - Hafsa Lakhal; Abdelfettah Seghir; Zahia Boucherit-Otmani; Abdeselem Benahmed (Microbes and Infectious Diseases, 2025)
Background: The tongue microbiome represents an important reservoir of pathogens, indicating an established risk for infections.The purpose of this study was to identify the tongue microbiota in subjects with and without oral diseases and compare oral health status between sexes. Methods: The sample consisted of 92 subjects, divided into the following groups: 17 xerostomia patients, 21 periodontitis patients, 22 gingivitis patients, 14 patients with caries, and 18 control participants. Samples were collected from the dorsal and ventral surfaces of the tongue for each subject. Microbial strains were identified using API and Vitek2. Results: There were no statistically significant differences in the detection of microorganisms between the two surfaces of the tongue (p= 0.706).The major isolated bacterial species from the tongue samples was Staphylococcus aureus (13% in xerostomia, 13% in gingivitis, 16% in periodontitis, 18% in caries and 24% in healthy subjects). While the most common fungal species was Candida albicans (39% in xerostomia,36% in gingivitis,18% in periodontitis, 25% in caries and 21% in healthy subjects).The distribution of yeast and bacteria varied between groups for certain species but was similar for other species. Moreover, there was a difference in susceptibility to oral diseases between males and females (p= 0.014). Conclusions: This study confirms the richness of the tongue in a variety of bacteria and fungi species in all groups and highlights the difference in susceptibility to oral diseases between sexes.